ELECTROSTATIC MASSAGE AND RADONOTHERAPY IN REHABILITATION OF VIBRATION NEUROPATHY PATIENTS - Гордеева, Раиса Васильевна; Филимонов, Сергей Николаевич; Кузьменко, Ольга Васильевна; Киреева, Лиана Николаевна (Medicine in Kuzbass, 2019)
Objective. The research objective is studying effective methods of rapid recovery of motor functions and sensitivity due to early relief of pain syndrome, prevention of formation of joint contractures, improvement of peripheral nerve conduction in vibration disease patients during rehabilitation based on the use of radon baths and electrostatic massage. Material and methods. The patients of the main group admitted for rehabilitation with vibration disease in the form of neuropathy of the extremities were prescribed electrostatic massage using the ELGOS device in the first half of the day and common radon baths from a natural source in the second half of the day. The control group of the patients received a classical manual massage and radon baths in a similar pattern. Before and after the treatment, studies of static-dynamic functions on the stabilometrical platform «BIOMECHANICS» were carried out, which determined the index of the total center of masses, the parameter of the cardiorespiratory system. Vibration sensitivity was evaluated. The assessment of the adaptation reaction was carried out according to L.G. Garkavi. Main results. Application of electrostatic massage and radon baths in the main group already after the second procedure allowed relieving pain syndrome and raising adaptation to functional loads on the musculoskeletal system, increasing the range of movements in the joints and restoring vibration sensitivity compared to the control group. All patients of the main group after the course of rehabilitation fully restored the range of movements while in the control group, motor limitations remained and periodically there was pain syndrome. They did not note full recovery of vibration sensitivity. Conclusions. The use of electrostatic massage and radon baths in the rehabilitation of vibration disease causes a more rapid recovery of the static-dynamic functions of the musculoskeletal system, the disappearance of pain syndrome, accelerates the recovery of sensitivity.